2019
DOI: 10.3390/su11082223
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Accident Severity for Curved Roadways Based on Bayesian Networks

Abstract: Crashes that occur on curved roadways are often more severe than straight road accidents. Previously, most studies focused on the associations between curved sections and roadway geometric characteristics. In this study, significant factors such as driver behavior, roadway features, vehicle factors, and environmental characteristics are identified and involved in analyzing traffic accident severity. Bayesian network analysis was conducted to deal with data, to explore the associations between variables, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Approximately 28 percent of total crashes occurred on horizontal curve segments, which are the second most common place for road crashes [4]. Even though more than half of total crashes happen on straight road segments, crashes on horizontal curves lead to more severe injuries owing to the complicated linear roadway conditions, unstable traffic speed, and dangerous driving conditions on curve segments referred to studies of Zhu et al [5] and Sustainability 2021, 13, 9011 2 of 18 Shi et al [6]. Moreover, previous studies by Hummer et al [7] and FHWA [8] found that the fatality rate from road crashes is three times higher on horizontal curves than other road segments, particularly with narrow lanes.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 28 percent of total crashes occurred on horizontal curve segments, which are the second most common place for road crashes [4]. Even though more than half of total crashes happen on straight road segments, crashes on horizontal curves lead to more severe injuries owing to the complicated linear roadway conditions, unstable traffic speed, and dangerous driving conditions on curve segments referred to studies of Zhu et al [5] and Sustainability 2021, 13, 9011 2 of 18 Shi et al [6]. Moreover, previous studies by Hummer et al [7] and FHWA [8] found that the fatality rate from road crashes is three times higher on horizontal curves than other road segments, particularly with narrow lanes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that accident frequency is affected by the segment length [21,24,29,32], lane width [29,40], lane numbers [27,32,38], carriageway width [21,29,41], and the shoulder width and type [29,42]. Significant attention has been dedicated to horizontal and vertical road geometric elements, which are found to affect the accident frequency [28,37,43,44]. Shankar et al [45] revealed that an increase in the number of horizontal curves at a road section leads to an increase in accident frequency.…”
Section: Factors Affecting the Accident Frequencymentioning
confidence: 99%
“…The results stated factors such as point of impact, site of location, accident side of road, and alcohol/drugs condition. They are very important in crashes in horizontal curves [20]. In 2018, Zhenning Li et al examined the severity of driver injuries at intersections, using cluster analysis and hierarchical Bayesian models.…”
Section: Literature Reviewmentioning
confidence: 99%